2011
DOI: 10.1021/jf2013937
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Risk Assessment of Four Typical Fluoroquinolone Antibiotics in Raw and Treated Sewage and in Receiving Waters in Hangzhou, China

Abstract: A sensitive liquid chromatography-fluorescence detection method, combined with one-step solid-phase extraction, was established for detecting the residual levels of the four typical fluoroquinolone antibiotics (ofloxacin, norfloxacin, ciprofloxacin, and enrofloxacin) in influent, effluent, and surface waters from Hangzhou, China. For the various environmental water matrices, the overall recoveries were from 76.8 to 122%, and no obvious interferences of matrix effect were observed. The limit of quantitation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 34 publications
0
28
1
2
Order By: Relevance
“…This result is consistent with the fact that OFL, NOR, and CIP are the most popular FQs consumed by humans in China (Table S4 †). 26 The other ve FQs, including DIF, ENR, FLE, LOM and SAR, were present at low concentrations (0.01-0.56 ng L À1 ) and detection rates (1-19% 29 China, indicating that the levels of FQs in Beijing were relatively high.…”
Section: Occurrence Of Antibiotics In Urban Surface Watermentioning
confidence: 99%
“…This result is consistent with the fact that OFL, NOR, and CIP are the most popular FQs consumed by humans in China (Table S4 †). 26 The other ve FQs, including DIF, ENR, FLE, LOM and SAR, were present at low concentrations (0.01-0.56 ng L À1 ) and detection rates (1-19% 29 China, indicating that the levels of FQs in Beijing were relatively high.…”
Section: Occurrence Of Antibiotics In Urban Surface Watermentioning
confidence: 99%
“…In Jinnan, the mean CIP level (5.10) is slightly lower than ENR (5.42). As indicated by Tamtam et al (2011), norfloxacin is a widely used FQ on the market since the late 80 s. And NOR, CIP, OFL and ENR are the main FQ antibiotics in China (Tong et al 2011). In addition, Picó and Andreu (2007) reported that CIP, ENR and OFL, which have high sorption coefficient K d values (61,000, 496-3,037, 44,100 L/kg, respectively), can move rapidly from the water compartment into solids due to their lipophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, due to the excessive addition in the feed, these drugs have also been frequently detected in environmental samples ascribing to the excretion via urine or feces. The concentration of ofloxacin in surface water bodies has been reported at 0.05 lg/L (Golet et al, 2002;Tong et al, 2011), and ciprofloxacin could reach as high as 5.93 lg/L for rivers contaminated by animal-farm effluents (Wei et al, 2012). In raw sewages and the secondary effluents from sewage treatment plants, 10 quinolones antibiotics were found and the concentrations ranged from 0.1 to 2.6 lg/L and 0.05 to 1.0 lg/L, respectively (Tong et al, 2011;Jia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of ofloxacin in surface water bodies has been reported at 0.05 lg/L (Golet et al, 2002;Tong et al, 2011), and ciprofloxacin could reach as high as 5.93 lg/L for rivers contaminated by animal-farm effluents (Wei et al, 2012). In raw sewages and the secondary effluents from sewage treatment plants, 10 quinolones antibiotics were found and the concentrations ranged from 0.1 to 2.6 lg/L and 0.05 to 1.0 lg/L, respectively (Tong et al, 2011;Jia et al, 2012). It is worth noting that ciprofloxacin have also been detected in untreated hospital sewages at a level of 101 lg/L (Lindberg et al, 2004;Martins et al, 2008).…”
Section: Introductionmentioning
confidence: 99%